KEPASTIAN HUKUM HAK GUNA BANGUNAN YANG TELAH BERAKHIR TERKAIT DENGAN SENGKETA PEWARISAN - Aldo Pratama Amry; Yuhelson, Yuhelson; Putra Hutomo (Journal of Innovation Research and Knowledge, 2025)
Conflicts and legal issues that arise due to the end of HGB and disputes between heirs. The formulation of the problem of this research is how the legal regulation of HGB that has ended and how the legal certainty of HGB that has ended is related to inheritance rights disputes. The theories used are the theory of legal certainty and the theory of dispute resolution.The method used in this research uses normative legal research, namely library legal research or secondary data with primary, secondary and tertiary legal material sources. The research approach used is a statutory, conceptual, case and analytical approach with legal material collection techniques by identifying and inventorying positive legal regulations, book literature, journals and other legal material sources with legal material analysis techniques carried out with grammatical, systematic interpretation and analogy construction.From the research, it can be concluded that Building Use Rights (HGB) are one form of land rights regulated in the UUPA, PP Number 18 of 2021, and Presidential Decree Number 32 of 1979. HGB that has expired can be extended with priority given to former HGB holders or legal heirs, as long as they meet requirements such as land use, spatial suitability, and legal documents. If not extended, the land will return to the state. In the context of inheritance, expired HGB can cause disputes. To ensure legal certainty, land registration is very important. Dispute resolution can be carried out through deliberation, mediation, or court, with legally binding decisions based on the principle of certainty.